Qur’an Based Human Resource Management in Developing Professional Competence Within Educational Institutions: A Qualitative Study at MI Al-Ma’had An-Nur - Malik, Muhammad Hisyam; Sumedi; Nadilla Aleyda Maqhfira Agustin (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study aims to provide a comprehensive depiction of human resource management (HRM) practices at MI Al-Ma’had An-Nur as aligned with values embedded in the Qur’an. Employing a qualitative descriptive research design, data were collected through observations, document analysis, and in-depth interviews with the head of the madrasah, a teacher, and a member of the internal quality assurance team, complemented by an analysis of relevant Qur’anic verses. The findings reveal that Qur’anic principles are operationalized in three core HRM dimensions: professional and merit-based recruitment, systematic monitoring and continuous capacity development, and the fulfillment of employee welfare. These practices have strengthened professional competence, integrity, and performance among teachers and educational staff, contributing to institutional effectiveness and rapid organizational growth. The study highlights the significance of integrating Islamic ethical values with modern HRM mechanisms as a viable framework for enhancing educational quality and organizational sustainability. However, the study is limited by its focus on a single institution and its reliance on qualitative data, which may constrain generalizability. Future research is recommended to involve multiple institutions and adopt comparative or mixed-methods approaches to further examine the broader applicability and impact of Qur’an-based HRM models in educational settings.